Impact of Climate Changes on Sheep Production in Marsa Matrouh Governorate in Egypt, using the Nardl Model Methodology - Fouzi Salih Faraj, (AlQalam Journal of Medical and Applied Sciences, 2026)
The study aimed to analyze the impact of positive and negative changes in the variables of maximum and minimum temperatures and rainfall on sheep production in Matrouh Governorate in Egypt. Nonlinear Autoregressive Distributed Lag (NARDL) modeling is used from 1998 to 2023. The results showed that negative changes in the maximum temperature (X1NEG) had a positive impact on sheep production, while positive changes in the rainfall variable (X3POS) hurt sheep production (Y) in the study area. Negative changes in the rainfall variable (X3NEG) had no impact. The error correction term coefficient (ECM (-1)) was -1.2490, a negative and statistically significant value. This indicates that sheep production returns to equilibrium after a short-term shock, with fluctuations occurring before stabilization due to excessive correction. In the matter of the long run, the positive changes in the variable X1 (maximum temperature) hurt sheep production. Changes in climatic factors, represented by positive and negative changes in maximum and minimum temperatures and rainfall, affect sheep production in the Marsa Matrouh region, and sheep production is affected by these non-linear and asymmetrical changes.